The Thematic Biography in the (Siya) Romance Novel: Focuses on the Biography of (Mamdoh Salim Beg) (Raparin Journal of Humanities (RJH), 2026)
The genres of biography and novel share a complex and interweaved relationship. This study, titled “ The Thematic Biography in the (Siya) Romance Novel “ , explores the biography of Mamdoh Salim Beg and inspects how factors of his life are mirrored within the ( Siya ) romance novel. The analysis targets to specifying whether the novelist’s narrative is purely imaginative or be affected by real-life experiences and events. Throughout a detailed comparison between Mamdoh Salim Beg’s actual life and the novel’s narrative structure , the research constructs the novel’s biographical nature. This study is segmented into two main sections. The first section discusses the definition of biography, variety kinds of biographies (autobiographical and topical), the connection between biography and the novel, and the relationship between the novel and history. The second section is structured into two main areas: The first area focuses on thematic biography within the ( Siya ) romance novel, delivering a brief biographical synopsis of Mamdoh Salim Beg aligned with a textual introduction. The second area analyzes Mamdoh Salim Beg’s As a result, we vhave come to the conclusion  thematic biography within the ( Siya ) romance novel the research consist introduction, conclusion, references, and a summary available in two languages: Kurdish and English.